Cardiac myosin binding protein-C variants in paediatric-onset hypertrophic cardiomyopathy: natural history and clinical outcomes. Issue 8 (16th August 2021) - Field, Ella; Norrish, Gabrielle; Acquaah, Vanessa; Dady, Kathleen; Cicerchia, Marcos Nicolas; Ochoa, Juan Pablo; Syrris, Petros; McLeod, Karen; McGowan, Ruth; Fell, Hannah; Lopes, Luis R; Cervi, Elena; et al.
Abstract : Background: Variants in the cardiac myosin-binding protein C gene ( MYBPC3 ) are a common cause of hypertrophic cardiomyopathy (HCM) in adults and have been associated with late-onset disease, but there are limited data on their role in paediatric-onset HCM. The objective of this study was to describe natural history and clinical outcomes in a large cohort of children with HCM and pathogenic/likely pathogenic (P/LP) MYBPC3 variants. Methods and results: Longitudinal data from 62 consecutive patients diagnosed with HCM under 18 years of age and carrying at least one P/LP MYBPC3 variant were collected from a single specialist referral centre. The primary patient outcome was a major adverse cardiac event (MACE). Median age at diagnosis was 10 (IQR: 2–14) years, with 12 patients (19.4%) diagnosed in infancy. Forty-seven (75%) were boy and 31 (50%) were probands. Median length of follow-up was 3.1 (IQR: 1.6–6.9) years. Nine patients (14.5%) experienced an MACE during follow-up and five (8%) died. Twenty patients (32.3%) had evidence of ventricular arrhythmia, including 6 patients (9.7%) presenting with out-of-hospital cardiac arrest. Five-year freedom from MACE for those with a single or two MYBPC3 variants was 95.2% (95% CI: 78.6% to 98.5%) and 68.4% (95% CI: 40.6% to 88.9%), respectively (HR 4.65, 95% CI: 1.16 to 18.66, p=0.03). Conclusions: MYBPC3 variants can cause childhood-onset disease, which is frequently associated with life-threatening ventricular arrhythmia. Clinical outcomes in this cohort vary substantially from aetiologically and genetically mixed paediatric HCM cohorts described previously, highlighting the importance of identifying specific genetic subtypes for clinical management of childhood HCM.